Delik Penghinaan Terhadap Pengadilan(Contempt Of Court) Dalam Perkara Pidana Di Indonesia - Amiruddin Amiruddin (Jurnal Penelitian Hukum Legalitas, 2015)
Contempt of Court, is a deliberate act that violates the authority of the court. Tends to obstruct and squandered the administration of justice, which is done at the mercy of the court by a party in the case and public, deliberately disobeyed lawful court orders. Contempt Of Court violations often occur either before, while, and after a trial held in court. But not infrequently violation Contempt Of Court, can occur in the judicial process at the level of investigation and prosecution of corruption cases and in the special criminal case, known as Obstruction of Justice.